Sejmiki ziemi zakroczymskiej 1778–1786 - Filipczak, Witold (Przegląd Nauk Historycznych, 2015)
The article concerns the Sejmiks in the land of Zakroczym, which belonged tothe Mazovian palatinate. During the debates in Zakroczym the szlachta electedtheir envoys to the sejm and candidates for the judiciary offices in the land ofZakroczym. They also settled the relevant issues connected with local selfgovernment.The article discusses preparations for the Sejmiks, their course andlauda. It also analyzes the instructions meant for representatives of the land ofZakroczym in Parliament. What made the land of Zakroczym special was thecontinual recurrence of the same postulates in the recommendations for successiveSejms. Even though the royalist influence was prevalent in the periodunder analysis the instructions for envoys in this particular land reflected thetraditional approach to the szlachta’s ethos. The fact that two out of four envoysfrom the land were later (1791) opposed to the Constitution of 3 May can beexplained in light of conservative tendencies in the Sejmik. The article also highlightsthe role of local political elite inspired by the subcamerarius of ZakroczymJózef Radzicki and the Kicki brothers (August and Onufry).